ANALYSIS OF LOCAL TAXES AND REGIONAL LEVIES CONTRIBUTIONS TO REGIONAL ORIGINAL REVENUE IN KEBUMEN REGENCY - Alya Firdawati; Erni Puji Astutik (Transpublika Publisher, 2022)
Local taxes and regional levies are a source of income for regional revenue (PAD). This study describes the contribution of local taxes and blood levies to regional revenue. This study aims to determine the growth of Local taxes and Regional Levies, determine the contribution of Local tax revenues and the contribution of Regional Levy revenues in Kebumen Regency in 2018-2020. The method used in this research is descriptive research with secondary data types obtained from published data, library materials, literature and previous research. This study uses growth and contribution analysis. The findings reveal that Regional Original Revenue is very dependent on Tax and Levies revenues. In 2018-2020, local tax growth averaged 4,64%. For the average tax contribution of 26,30%, while the average contribution of regional levies is 8,67%.